Clinical Utility of the Detection of the Loss of the Mismatched HLA in Relapsed Hematological Patients After Haploidentical Stem Cell Transplantation With High-Dose Cyclophosphamide - Muñiz, Paula; Kwon, Mi; Carbonell, Diego; Chicano, María; Bailén, Rebeca; Oarbeascoa, Gillen; Suárez-González, Julia; Andrés-Zayas, Cristina; Menárguez, Javier; Dorado, Nieves; Gómez-Centurión, Ignacio; Anguita, Javier; et al. (Frontiers in Immunology, 2021)
Haploidentical hematopoietic stem cell transplantation (Haplo-HSCT) with high-dose cyclophosphamide (PTCy) has resulted in a low incidence of graft-versus-host disease (GVHD), graft failure, and non-relapse mortality. However, post-transplantation relapse remains a common cause of treatment failure in high-risk patients Unraveling the mechanisms of relapse is therefore crucial for designing effective relapse treatment strategies. One of these mechanisms is the loss of the mismatched HLA on the recipient’s leukemic cells. To study the incidence and clinical relevance of this phenomenon, we analyzed 181 patients treated with Haplo-HSCT with PTCy (2007-2019), of which 37 relapsed patients after transplantation. According to the kit employed for HLA-loss analysis, among 22 relapsed patients, we identified HLA loss at relapse in 6 of the 22 patients (27%) studied. Based on the results obtained, the genomic loss of HLA was more common in females than males (66% vs. 33%) and the HLA-loss relapses occurred later than classical relapses (345 vs. 166 days). Moreover, the patients with HLA-loss had a greater presence of active disease at the time of transplantation and had undergone a larger number of treatment lines than the group with classical relapses (66% vs. 43% and 66% vs. 18%, respectively). Four of these relapses were studied retrospectively, while 2 were studied prospectively, the results of which could be considered for patient management. Additionally, 2 relapsed patients analyzed retrospectively had myeloid neoplasms. One patient had not undergone any treatment, and 3 had undergone donor lymphocyte infusions (DLIs) and chemotherapy. All presented severe GVHD and disease progression. In contrast, the 2 patients studied prospectively had a lymphoid neoplasm and were not treated with DLIs. One of them was treated with chemotherapy but died from disease progression, and the other patient underwent a second Haplo-HSCT from a different donor and is still alive. We can conclude that the detection of HLA-loss at the onset of relapse after Haplo-HSCT with PTCy could help in clinical practice to select appropriate rescue treatment, thereby avoiding the use of DLIs or a second transplantation from the same donor.